Analysis of the Landfill Leachate Treatment System Using Arima Models: A Case Study in a Megacity - Carlos Alfonso Zafra-Mejía; Daniel Alberto Zuluaga-Astudillo; Hugo Alexander Rondón-Quintana (Applied Sciences, 2021)
Leachate has been reported as the most significant source of landfill pollution. Predicting the characteristics of untreated and treated leachate may be useful during optimal scheduling of leachate treatment systems. The objective of this paper is to show an analysis of the operation of a landfill leachate treatment system in a Latin American megacity (Bogota, Colombia) by means of auto-regressive integrated moving average (ARIMA) models. A comparative analysis of the leachate treated with respect to reference legislation is carried out. The influence of climate variables during the operation of the treatment system is also considered. The results suggest that the concentrations of heavy metals (HMs), BOD5, and COD in untreated leachate do not follow the same annual cycles observed for the quantity of solid waste disposed within the landfill. This difference is possibly associated with the hydraulic retention time (HRT) of the leachate inside the conduction and pre-treatment system (storage/homogenization ponds). The ARIMA analysis suggests an HRT of up to one month (AR = 1) for the HMs identified as indicators of untreated leachate (Cu, Pb, and Zn). It is noted that the removal efficiency of HM indicators of the operation of the leachate treatment plant (Fe and Ni) is probably conditioned by operations carried out over a period of one month (AR = 1). The high input concentration of these HM indicators may prevent changing their ARIMA temporal structure during leachate treatment. This is reflected in the low removal efficiencies for all HMs under study (average = 26.1%).